Pemanfaatan Information and Communication Technology (ICT) dalam Pembelajaran di SD/MI - Mohamad Munawar (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
This research falls under the category of field research, conducted directly at SD Muhammadiyah 1 Blora. The main focus of this study is the collection and documentation of data carried out on-site at the research location. The method used in this study is replication research. Replication research is a type of scientific study conducted with the aim of repeating, verifying, or strengthening the results of previous research. In practice, replication research employs designs, methods, or instruments similar to those used in prior studies, but may be conducted in different contexts, times, populations, or conditions. The utilization of Information and Communication Technology (ICT) in education contributes significantly to improving the quality of the teaching and learning process. ICT supports mass or classical learning by introducing interactive media that helps teachers effectively deliver materials to a large number of students. Moreover, ICT assists students in independent learning by providing access to a variety of digital learning resources anytime and anywhere, thereby fostering critical thinking skills and a sense of responsibility toward their own learning process. Furthermore, ICT facilitates educational administration management through efficient, transparent, and integrated information systems, which enhance the overall performance of schools. The implementation of ICT also contributes to the development of students’ character in elementary education, such as fostering self-confidence, creativity, responsibility, and adaptability to technology. In conclusion, the integration of ICT in education not only enhances academic achievement but also helps shape students’ character and competence to face the challenges of the digital era. Keyword: Education, Elementary school, Information and Communication Technology (ICT)